In Search for a Viable Smart Product Model - Barata, João (2019)
Smart products integrate physical and digital materialities, taking advantage of sensors, mobile technologies, and advanced data processing capabilities. This type of systems is a top priority for managers, offering the capacity to sense, communicate, adapt, and anticipate the needs of business stakeholders. We use the lens of the Viable System Model (VSM) theory to align business strategies and smart products. The proposed model was tested in a real case of information systems development for safety in construction. The findings emerge from a design science research that is part of a larger project to introduce smart technologies in the construction industry. A viable product model (VPM) represents the necessary and sufficient conditions for the smart product cohesion and endurance in different environments, aligned to the business needs. For theory, we present a product-level adoption of VSM and propose guidelines for business-smart product alignment. For practice, the results can assist managers in creating new smart products that adhere to their strategy and capable of dealing with unexpected events.